Where is occupational health and safety management research in small and medium-sized enterprises headed? A thematic evolution and bibliometric analysis - Salguero-Caparrós, Francisco Miguel; Sánchez-Teba, Eva María; Bermúdez-González, Guillermo José; Rubio-Romero, Juan Carlos (Taylor & Francis, 2025)
Without a doubt, small and medium-sized enterprises (SMEs) are one of the European economy’s great strengths as they employ over half of the total workforce. As a result, the current EU-OSHA strategy for 2022–2027 emphasizes the need to pay special attention to the specific problems of SMEs in order to improve health and safety management in these organizations. The objective of this study is to analyze the existing research gaps and from this point to trace future research lines in terms of the thematic evolution in the field of research on health and safety management specifically in SMEs through an exhaustive bibliometric analysis, in terms of both structure and concept. We used the Science Mapping Analysis Software Tool (SciMAT) program, an open-source software tool that builds scientific maps in a longitudinal framework, to identify the main topics covered within this thematic area over time. This bibliometric analysis concludes that it is essential to broaden knowledge about conceptual models for workplace risk analysis and assessment in order to boost occupational health and safety management performance with a special interest among SMEs. The emphasis is on integrating the Resilience Engineering paradigm and the emerging Safety II approach to address these challenges effectively.
Keywords: Pequeñas y medianas empresas - Medidas de seguridad; Seguridad industrial; Small and medium-sized enterprises; Occupational risk prevention; Safety management; Key themes; Resilience engineering